The SAGE handbook of media processes and effects - Nabi, Robin L.; Oliver, Mary Beth (Sage Publications, Inc., 2009)
Comprehensive exploration of where media effects research has been in the last 20 years, andwhat the future might hold for the field as rapid changes in the media environment continue